(untitled) (Current Horticulture, 2024)
Sixtysix genotypes of French bean (Phaseolus vulgaris L.) were evaluated for correlation and path coefficient analysis at KRCCH, Arabhavi, University of Horticultural Sciences, Bagalkot.. In most cases, genotypic correlations were higher than phenotypic correlations indicating highly heritable nature of green pod yield/plant which showing positive and significant correlation with plant height at 60 days after sowing, number of branches/plant at 60 days after sowing and 100 seed weight both at genotypic and phenotypic level, whereas number of branches per plant at 30 days after sowing, number of pods/plant and number of seeds/plant showed positive and significant correlation at genotypic level only. Path coefficient revealed that number of branches/plant at 60 days after sowing and pod weight characters have direct positive effect on green pod yield per plant. Thus, these characters deserve greater weightage during selection for yield. The direct selection in these traits would be rewarding for improvement in the pod yield/plant.